The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1472-6882-12-196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginsenoside Re on LPS-induced inflammatory mediators in BV2 microglial cells

Abstract: BackgroundMicroglial activation plays an important role in neurodegenerative diseases by producing several pro-inflammatory enzymes and pro-inflammatory cytokines. Lipopolysaccharide (LPS)-induced inflammation leads to the activation of microglial cells in the central nervous system (CNS) and is associated with the pathological mechanisms of neurodegenerative diseases, including PD, AD, and ALS. Ginseng is a natural antioxidant used in herbal medicine and contains ginsenosides (Rb1, Rg1, Rg3, Re, and Rd), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 35 publications
2
40
0
1
Order By: Relevance
“…Excessive inflammation plays a pivotal role in the pathogenesis of organ injury, especially in the heart. LPS is widely used to induce inflammation response, as evaluated by increase of pro-inflammatory cytokines (Lee et al, 2012a). What is more, MMPs, which is increased upon exposure to LPS, can provoke inflammatory signaling in remodeling process (DeLeon-Pennell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive inflammation plays a pivotal role in the pathogenesis of organ injury, especially in the heart. LPS is widely used to induce inflammation response, as evaluated by increase of pro-inflammatory cytokines (Lee et al, 2012a). What is more, MMPs, which is increased upon exposure to LPS, can provoke inflammatory signaling in remodeling process (DeLeon-Pennell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among ginsenosides, ginsenoside Re, Rd, and Rg1 are known to be mainly present in the ginseng leaves (Kim et al 2015). Lee et al have showed that ginsenoside Re may lead to an anti-neuro inflammatory effect on p38 signaling in LPS-induced BV2 microglial cells (Lee et al 2012). Moreover, Wu et al indicated that the divergent structure of the ginsenosides including Re, Rd, and Rg1, are responsible for the anti-inflammatory effects in LPS-induced N9 microglial cells by blocking NF-jB signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These ginsenosides have been reported to show various biological activities, including anti-inflammatory activity. Commonly studied ginsenosides such as both protopanaxatriol-type ginsenosides Rg1, Re and protopanaxadiol-type ginsenosides Rb2, Rd demonstrate anti-inflammatory effects [19, 20]. Recently, results have shown that compound K transformed from Rb2 is effective against inflammation [21].…”
Section: Discussionmentioning
confidence: 99%